A framework to guide future farming research with Indigenous communities - Daniel Hayden; Amber Hayden (Journal of Agriculture, Food Systems, and Community Development)
We present a framework to guide applied research with Indigenous Peoples. Indigenous cropping systems are relevant to scientifically addressing many of the shortcomings and problems regarding current cropping systems. Indigenous food sovereignty movements are currently preserving and expanding their cropping system food ways. The knowledge underlying these efforts is not static but dynamic, incorporating contemporary tools in ever changing environments. We highlight four principles of Indigenous farming that are reflected in both practice and cultural traditions: polycultures, seed-keeping, sustainability, and community. These principles have been pivotal to the primary author’s doctoral research as they collaborate with Indigenous communities in Wisconsin to trial organic farming practices that utilize their traditional values and knowledge. We encourage more applied research in farming and natural sciences that uphold Indigenous ways of knowing as equal to Western science through collaborating with Indigenous Peoples. Researchers should be aware of the implications of research in Indigenous communities, involving the cultural boundaries associated with crops and seeds, which are often not regulated and thus warrant protection. As Western science seeks to find sustainable alternatives to current farming norms, as seen in other areas of land management, we encourage creating shared learning environments between researchers and Indigenous Peoples to foster relevant and equitable outcomes for farming practices.